Being Vulnerable: A Qualitative Inquiry of Physician Touch in Medical Education. (December 2020) - Kelly, Martina; Nixon, Lara; Rosenal, Tom; Crowshoe, Lindsay; Harvey, Adrian; Tink, Wendy; Dornan, Tim
Abstract : Purpose: Effective nonverbal communication is associated with empathic behavior and improved patient outcomes. Touch, as a form of nonverbal communication, is relatively unexplored in medical education. This study sought to gain in-depth insights into physicians' experiences communicating with touch and to examine how these insights could inform communication skills curricula. Method: Collaborative inquiry, a form of action research, was used. Six experienced physician–educators from the University of Calgary met 8 times between 2015 and 2018 to critically reflect on their experiences of touch in clinical practice, teaching, and learning. Data comprised meeting transcripts, individual narrative accounts, and digital recordings of role-plays. Interpretative phenomenology, the study of lived experience, guided analysis. Results: Two themes were identified—touch as presence and touch as risk. Participants used touch to demonstrate presence and a shared humanity with patients, to express "being with" a patient. Risk was not associated with the physical experience of touch but, rather, with its social meaning, interpreted through gender, culture, relationships, and context. Individual experiences were open to many interpretations. Participants expressed tension between their personal experience communicating with touch to express empathy and formal curricular structures. Reflection, role-modeling, and clinical debriefs were suggested as ways to encourage situational awareness and sensitive use of touch. Conclusions: Touch is a powerful means to communicate with patients but is highly subjective. Rather than avoiding touch for fear of misinterpretation, encouraging dialogue about its complexity could promote a more balanced understanding of touch and its potential to convey empathy and help physicians more effectively manage risk when using touch. Abstract : Supplemental Digital Content is available in the text.